Welding of Normalized Heat Treated Steels S355NL Large Thicknesses by Method FCAW - Kolaříková, Marie; Kolařík, Ladislav; Kovanda, Karel; Hrabina, Rudolf (Manufacturing Technology Journal, 2013)
Welding of thick plates of heat treated steels present difficulties, because of decrease of mechanical properties caused by welding heat input. At Welding Department of FME of CTU in Prague experiments researching influence of use cored wire on FCAW welding of thick plate welding was done. Plate of fine grained structural steel S355NL of thickness 50 mm used for crane fabrication was subjected to FCAW welding. Double-V butt joint was welded using flux cored wire (Coreweld 46 LS) as filler metal. The welded crane structure needs WPS certification, so WPQR tests were done. The paper presents welding procedures and results of non-destructive (visual, magnetic and radiographic testing) and destructive (tensile test, Charpy impact test, metallography, hardness measurement and bending test) tests of weld joint.
Keywords: FCAW; fine grained steel; S355 NL; X-rays; visual testing